Nucleotides Bearing Red Viscosity-Sensitive Dimethoxy-Bodipy Fluorophore for Enzymatic Incorporation and DNA Labeling - Kuba, Miroslav; Pohl, Radek; Kraus, Tomáš; Hocek, Michal (Bioconjugate chemistry, 2023)
Nucleosides and 2'-deoxyribonucleoside triphosphates (dNTPs) bearing 3,3'-dimethoxy-2,2'-diphenyl-6-(4-hydroxyphenyl)-bodipy fluorophore attached through a propargyl or propargyl-triethylene glycol linker to position 5 of 2'-deoxycytidine were designed and synthesized. They exerted bright red fluorescence and good sensitivity to viscosity changing their lifetime from 1.6 to 4.5 ns. The modifed dNTPs were substrates for DNA polymerases and were used in enzymatic synthesis of labeled DNA through primer extension. The modified DNA probes served as viscosity sensors responding to protein binding by changes of lifetime. The nucleotide with longer linker (dCpegMOBTP) was transported to live cells and incorporated into the genomic DNA, which can be useful for staining of DNA and imaging of DNA synthesis.
Keywords: Viscosity; viskozita; nukleosidy; Nucleosides; DNA; DNA-Directed DNA Polymerase; nukleotidy; DNA-dependentní DNA-polymerasy; Nucleotides